Screening for haemorrhagic disorders in paediatric patients by means of a questionnaire - Music, I.; Novak, M.; Acham-Roschitz, B.; Muntean, W. (Hämostaseologie, 2009)
Aim: In children, screening for haemorrhagic disorders is further complicated by the fact that infants and young children with mild disease in many cases most likely will not have a significant history of easy bruising or bleeding making the efficacy of a questionnaire even more questionable. Patients, methods: We compared the questionnaires of a group of 88 children in whom a haemorrhagic disorder was ruled out by rigorous laboratory investigation to a group of 38 children with mild von Willebrand disease (VWD). Questionnaires about child, mother and father were obtained prior to the laboratory diagnosis on the occasion of routine preoperative screening. Results: 23/38 children with mild VWD showed at least one positive question in the questionnaire, while 21/88 without laboratory signs showed at least one positive question. There was a trend to more specific symptoms in older children. Three or more positive questions were found only in VWD patients, but only in a few of the control group. The question about menstrual bleeding in mothers did not differ significantly. Sensitivity of the questionnaire for a hemostatic disorder was 0.60, while specifity was 0.76. The negative predictive value was 0.82, but the positive predictive value was only 0.52. Conclusions: Our small study shows, that a questionnaire yields good results to exclude a haemostatic disorder, but is not a sensitive tool to identify such a disorder.
Keywords: Von Willebrand disease